Using a Cavitation Model to Represent the Acoustic Release Kinetics from Folated Micelles - Tanbour, Rafeeq Kamal (2014)
A Master of Science thesis in Chemical Engineering by Rafeeq Kamal Tanbour entitled, "Using a Cavitation Model to Represent the Acoustic Release Kinetics from Folated Micelles," submitted in December 2014. Thesis advisor is Dr. Ghaleb Husseini. Available are both soft and hard copies of the thesis.